The impact of the great recession on school district finances: Evidence from New York - Rajashri Chakrabarti; Elizabeth Setren (Federal Reserve Bank of New York, 2011)
Despite education's fundamental role in human capital formation and growth, there is no research that examines the effect of the Great Recession (or any other recession) on schools. Our paper begins to fill this gap. Exploiting detailed data on school finance indicators and an analysis of trend shifts, we examine how the Great Recession affected school funding in New York State. While we find no evidence of effects on either total revenue or expenditure, there were important compositional changes to both. There is strong evidence of substitution of funds on the revenue side - the infusion of funds from the federal stimulus occurred simultaneously with statistically and economically significant cuts in state and local financing, especially the former. On the expenditure side, instructional expenditure was maintained, while other categories such as transportation, student activities, and utilities suffered. Important heterogeneities in experiences are also observed by poverty level, metropolitan area, school district size, and urban status. Affluent districts were hurt the most; the New York City metro area, especially Nassau County, sustained the largest losses in terms of both revenue and expenditure. Our findings promise to facilitate an understanding of how recessions affect schools and of the role policy can play in mitigating the consequences.
Keywords: H40; I21; I28; 330; school finance; recession; American Recovery and Reinvestment Act; federal stimulus